PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH E-WOM TERHADAP PURCHASE INTENTION - Rohman, M. Uky Taufiqur; Respati, Ni Nyoman Rsi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Advances in technology have changed the style of society in conducting social interactions, nowadays social interactions can be done using technology and even buying and selling interactions can be done online. Internet users in Bali in 2018 are still centered in Denpasar City as much as 66.11 percent, therefore the Bukalapak company can increase the Purchase Intention of the Denpasar community. This study aims to determine the role of Brand Image in mediating the effect of e-WOM on Purchase Intention. This research was conducted at Bukalapak company in Denpasar. The sample used in this research amounted to 120 respondents using purposive sampling method. The data analysis technique used is path analysis. Data collection was done by distributing questionnaires via google form. The results of this study indicate that the e-WOM variable has a positive and significant effect on Purchase Intention at Bukalapak in Denpasar, e-WOM has a positive and significant effect on Brand Image on Bukalapak in Denpasar, Brand Image has a positive and significant effect on Purchase Intention on Bukalapak in Denpasar, Brand Image is a variable mediating the effect of e-WOM on Purchase Intention on Bukalapak in Denpasar.